DESIGN OF ACCOUNTING RECORDING SYSTEM IN KOPERASI KARYAWAN KUSUMA UPND - Erna Wati; Olivia Rebeca Tamaris Gultom (Universitas Internasional Batam, 2022)
Koperasi Karyawan Kusuma has been running its business for 17 years. Over time, Koperasi Kusuma expanded its business by increasing the number of services provided. Therefore, it is necessary to have an adequate accounting record system to record the number of transactions that occur. Koperasi Kusuma's operational activities have been going well by carrying out the necessary transactions to support business activities. However, this cooperative transaction recording system is carried out manually, namely recording on books and applications Microsoft Excel. By maintaining a financial recording system like this when the business is growing, the process of recording transactions and making financial reports will be longer, more complicated, and there are still some transactions that are missed to be recorded. With a slight error in financial records, the financial statements that will be produced will not be balanced. The worker doing the record keeping will need extra time to correct the imbalance. The purpose of this activity is to help overcome the obstacles of accounting records in Koperasi Kusuma SMEs by designing an accounting recording system. The stages of implementing this practical work are through interviews and observations in collecting information, designing a recording system made by the author, conducting system simulations with the previous year's cooperative financial data, and implementing the system on MSMEs. The result of this practical work activity is a simple accounting record system that can produce financial reports and can be used for future decision making.